Duval County 2009, 2011, and 2013 Fruit and Vegetable Intake by Health Zone: Data from the Youth Risk Behavior Survey - Zhiping Yu; Alireza Jahan-Mihan; Corinne A. Labyak; Claudia Sealey-Potts; Catherine Christie; Judith Rodriguez; Janice J Seabrooks-Blackmore; Karen Patterson; Richard Patterson (University of North Florida, 2016)
The purpose of this study was to compare the results of fruit and vegetable intake data from the 2009, 2011, 2013 Duval County Youth Risk Surveys (YRBS) by health zone. The survey instrument (questionnaire) is administered using a cluster sample design in all ninth grade classes in public schools (except charter schools) every two (odd) years. The surveys are anonymous and there is parental notification. Oversampling is done to allow for sub-county analysis. There were no statistically significant differences across health zones for any of the fruit and vegetable consumption questions for year 2009 however all health zones were below the recommended level of fruit and vegetable intake. For years 2011 and 2013 despite significant statistical differences by health zone in the frequency of consumption for fruits and vegetables, all health zones had a low mean intake of fruits and vegetables for years 2009, 2011 and 2013. Most respondents indicated consuming fruits, green salad, potatoes (not fried), carrots and vegetables "1 to 3 times during the past 7 days." Overall intake of fruits and vegetables, however, was low for all health zones.